On the justification of Koiter’s model for elliptic membrane shells subjected to an interior normal unilateral contact condition - Piersanti, Paolo (Nonlinear analysis: real world applications, 2026)
The purpose of this paper is twofold. First, we rigorously justify Koiter’s model for linearly elastic elliptic membrane shells in the case where the shell is subject to a geometrical constraint modelled via an interior normal unilateral contact condition defined in the interior of the shell. To achieve this, we establish a novel density result for non-empty, closed, and convex subsets of Lebesgue spaces, which are applicable to cases not covered by the “density property” established in Ciarlet et al. (2019). Second, we demonstrate that the solution to the two-dimensional obstacle problem for linearly elastic elliptic membrane shells, subjected to the interior normal unilateral contact condition, exhibits higher regularity throughout its entire definition domain. A key feature of this result is that, while the transverse component of the solution is, in general, only of class L2 and its trace is a priori undefined, the methodology proposed here, partially based on Ciarlet and Sanchez-Palencia (1996), enables us to rigorously establish the well-posedness of the trace for the transverse component of the solution by means of an ad hoc formula.